Fabrication and electrochemical evaluation of micro-supercapacitors prepared by direct laser writing on free-standing graphite oxide paper - Kumar, Rajesh; Joanni, Ednan; Savu, Raluca; Pereira, Matheus S. [UNESP]; Singh, Rajesh K.; Constantino, Carlos J. L. [UNESP]; Kubota, Lauro T.; Matsuda, Atsunori; Moshkalev, Stanislav A. (Elsevier B.V., 2019)
This article presents results of a pulsed UV laser method for the simultaneous reduction of graphite oxide (GO) and patterning of reduced graphene oxide (rGO). This direct laser writing method was applied to the fabrication of graphene-based, in-plane interdigitated micro-supercapacitors (mu-SCs), prepared on free-standing GO paper (10 mu m thick). The electrochemical performance of mu-SCs was studied using two different electrolytes (KOH and NaCl). The results from cyclic voltammetry measurements exhibited typical electrical double layer behavior, with specific capacitances of 9.3 mu F/cm(2) and 13.8 mu F/cm(2) (at a scan rate of 10 mV/s) for KOH and NaCl electrolytes, respectively. The mu-SCs exhibited good performance, with retention of 95% of the original capacitance values after 3400 charge-discharge cycles. When compared to devices obtained by conventional lithographic techniques, the laser fabrication of planar mu-SCs is faster, cost-effective and scalable. We believe this one-step and environmentally friendly laser-assisted method to be a good alternative for the fabrication of flexible energy storage devices. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: GO paper; Pulsed laser; Direct laser writing; mu-supercapacitors; Areal capacitance; Cycling stability